Long-Term Outcomes of Laminectomy in Lumbar Spinal Stenosis: A Systematic Review and Meta-Analysis - Sajadi, Kiavash; Azarhomayoun, Amir; Jazayeri, Seyed Behnam; Baigi, Vali; Ranjbar Hameghavandi, Mohammad Hosein; Rostamkhani, Sabra; Atlasi, Rasha; Faghih Jooybari, Morteza; Ghodsi, Zahra; Vaccaro, Alexander R.; Khorasanizadeh, MirHojjat; Rahimi-Movaghar, Vafa (Asian Journal of Neurosurgery, 2022)
Objective Lumbar spinal stenosis (LSS) patients suffer from significant pain and disability. To assess long-term safety and efficacy of laminectomy in LSS patients, a systematic review and meta-analysis study was conducted.Methods Literature review in MEDLINE, Embase, Scopus, Web of Science, and Cochrane Library databases was performed using a predefined search strategy. Articles were included if they met the following characteristics: human studies, LSS, and at least 5 years of follow-up. Outcome measures included patient satisfaction, pain, disability, claudication, reoperation rates, and complications.Results Twelve articles met the eligibility criteria for our study. Overall, there was low-quality evidence that patients undergoing laminectomy, with at least 5 years of follow-up, have significantly more satisfaction, and less pain and disability, compared with the preoperative baseline. Assessment of neurogenic intermittent claudication showed significant improvement in walking abilities. We also reviewed the postoperative complication and adverse events in the included studies. After meta-analysis was performed, the reoperation rate was found to be 14% (95% confidence interval: 13–16%).Conclusion Our study provides low-quality evidence suggesting that patients undergoing laminectomy for LSS have less disability and pain and can be more physically active postoperatively.
Keywords: laminectomy; spinal stenosis; lumbar spinal stenosis; intermittent claudication